New Clause in Bank Credit Agreement in Relation to Consumer Protection Act - Yustika Dewi; Ngr. Tini Rusmini Gorda (Universitas Warmadewa, 2021)
The importance of banking institutionsâ€™ existence in one side provide very high risk for banks and in the other side provide profit for public as fund userâ€™s clients. Standard contract circulating in public seen from viewpoint of many parties is still detrimental with clauses presence in the contract. The content of standard contract in general is biased because it tends to benefit the contract maker. The standard contract if seen from the legal side is still being debated in terms of principles and validity requirement of an agreement. The inclusion of this clause shows the strength of creditorâ€™s position which actually already strong despite without the inclusion of this clause. In banking practice, it is found in credit granting by bank the inclusion of unilateral terms which states that â€œthe bank at any time is allowed to change the interest rate beforehandâ€ in the contract that has been standardized previously by the bank. Credit agreement in standard form which is being made unilaterally by the bank until present is still becoming a special legal issue in agreement field of civil law. In addition, viewed from the side of the agreement it is also against consumer protection law as set in Consumer Protection Act. Problem formulation of this thesis is divided into namely regarding the existence of standard clause in bank agreement if associated with Article 18 of Consumer Protection Act and legal consequence of standard clause in credit agreement associated with consumer protection. The research in this thesis is Juridical empirical. The author is guided by laws and regulations related with public fact, that is first problem formulation is analyzed from balancing principle and next the second problem formulation is from consumer protection theory.